Nevsun V. Araya: A Blueprint for Protecting Human Rights Through Tort Law - Ezra Isaacs (Washington University Global Studies Law Review, 2023)
An important issue affected by the globalization of the world’s economy is the distribution of worldwide labor through outsourcing of production. Political discourse related to this issue has focused on its impact on employment for many working class citizens who have experienced less demand for their services. Indeed, many politicians have campaigned on promises to bring jobs back home. Another concern is that corporate wage savings are facilitated by the lower leverage and protection for workers in countries with lax employment laws. Even though domestic corporations may not intend to incorporate forced labor or other human rights abuses into their supply chains, it is important to hold corporations accountable for indifference to such practices. There are several potential solutions, but each involves sensitive considerations because of the multinational nature of modern industry. Traditionally, international law has centered around notions of state sovereignty, which limits the scope of feasible approaches to human rights issues in the global supply chain, since they occur abroad. Governments are measured and careful in their rebuke of foreign governments even for offences that could be considered outrageous if they occurred domestically. However, over the past century, state sovereignty has come into tension with universal human rights, which has arguably transformed international law, placing constraints on sovereigns’ powers and their agents when conducting war or otherwise engaging in conflict. Indeed, treaties and international agreements have paved the way for international criminal proceedings against individuals, shaping international attitudes in favor of prosecuting agents of sovereign powers who previously were immune from punishment. A key aspect of this evolution was the recognition that human rights transcend the relationship between citizens and their governments, and that governments cannot be allowed to deprive any person of universal rights, regardless of state sovereignty.
Keywords: Tort Law; Human Rights; International Law; State sovereignty; global supply chain; universal rights; Civil remedies; Alien Tort Statute; Corporations; Canada; United States